Regionalization through Media Consumption: The Consumption of Thai and Filipino Soap Operas among Vietnamese Audiences - NGUYEN THI TU ANH (Journal of Social Sciences, Faculty of Social Sciences, Chiang Mai University, 2020)
Journal of Social Sciences is the academic journal published by Faculty of Social Sciences, Chiang Mai University since 1970. The journal’s editor and its editorial team members are those academics who are from both inside the Faculty of Social Sciences and from other leading Social Sciences faculties in Thailand. The aim of this journal is to publish a high-quality work and/or a research finding, particularly in Anthropology, Development Studies, Geography, Sociology and Women Studies to the public. Later in the year 2018, the Journal of Social Sciences Faculty of Social Sciences Chiang Mai University Has started producing journals in electronic format (Online).